Inhabited Ideology: Diversity Ideology and Approaches to Racial Equity Across Institutional Sectors - Emily Handsman; Bonnie Siegler (Socius)
Sociologists study diversity as both the cornerstone idea of an emergent dominant racial ideology and an organizational strategy to address racial inequality. How do diversity workers adapt this ideology to the institutional demands of their organizational contexts? The authors bring research on racial ideology and inhabited institutionalism together to propose a theory of inhabited ideology by showing that institutional myths—cultural ideals that organizations must engage with to maintain legitimacy within their institutional sector—mediate diversity ideology to create local ideological tenets which shape and justify organizational approaches to racial equity. The authors use two case studies to show that workers charged with addressing racial inequality in public and private K–12 schools interpret the demands of their work and develop racial equity programming in ways that align with sector-specific institutional myths. The authors argue for additional uses of this theory to examine the intersection of ideology and organizational diversity, equity, and inclusion efforts across sectors.